Overexpression of the potato VQ31 enhances salt tolerance in Arabidopsis - Zhai, Mingming; Ao, Zhengxiong; Qu, Haoran; Guo, Dongwei (Frontiers in Plant Science, 2024)
Plant-specific VQ proteins have crucial functions in the regulation of plant growth and development, as well as in plant abiotic stress responses. Their roles have been well established in the model plant Arabidopsis thaliana; however, the functions of the potato VQ proteins have not been adequately investigated. The VQ protein core region contains a short FxxhVQxhTG amino acid motif sequence. In this study, the VQ31 protein from potato was cloned and functionally characterized. The complete open reading frame (ORF) size of StVQ31 is 672 bp, encoding 223 amino acids. Subcellular localization analysis revealed that StVQ31 is located in the nucleus. Transgenic Arabidopsis plants overexpressing StVQ31 exhibited enhanced salt tolerance compared to wild-type (WT) plants, as evidenced by increased root length, germination rate, and chlorophyll content under salinity stress. The increased tolerance of transgenic plants was associated with increased osmotic potential (proline and soluble sugars), decreased MDA accumulation, decreased total protein content, and improved membrane integrity. These results implied that StVQ31 overexpression enhanced the osmotic potential of the plants to maintain normal cell growth.Compared to the WT, the transgenic plants exhibited a notable increase in antioxidant enzyme activities, reducing cell membrane damage. Furthermore, the real-time fluorescence quantitative PCR analysis demonstrated that StVQ31 regulated the expression of genes associated with the response to salt stress, including ERD, LEA4-5, At2g38905, and AtNCED3. These findings suggest that StVQ31 significantly impacts osmotic and antioxidant cellular homeostasis, thereby enhancing salt tolerance.